Inovação e desenvolvimento regional no Brasil : indicadores de desempenho e mecanismos de financiamento - Souza, Vanusa Maria de (2016)
The innovation and the technological progress are considered fundamental themes for economic development of the country, being directly related to increased firms competitiveness. This is reflected even when the subject involves regional development, with implications for productivity and firms performance. Considering the high financial costs and the risks and uncertainties inherent in the innovation process, it is essential to observe financing policies required in this process, particularly with the participation of public funding agencies. In Brazil, these policies are consolidated from the “Lei de Inovação (nº 10.973/2004)”, the “Lei do Bem (nº 11.196/2005)” and the new legal march in Science, Technology and Innovation (nº 13.243/2016), seeking provide a favorable environment for innovation and scientific and technological research in the national and regional productive system of the country. This study aimed to analyze the evolution of technological innovation and public funding to regional innovation activities. For this, a descriptive statistical analysis of the performance of innovative indicators was carried out, from the data provided by the Technological Innovation Research (PINTEC) – editions in 2005, 2008 and 2011 – the National Institute of Industrial Property (INPI), the Funding of Studies and Projects (FINEP) and the National Bank for Social and Economic Development (BNDES), covering the period 2005-2014. The results confirm the positive evolution of Technology innovation in all regions of Brazil - as the number of beneficiary firms and the volume of funds granted - but the data indicate a higher concentration of public resources for innovation in the Southeast region, followed by the South region, representing a percentage of approximately 90% of the total invested in Brazil, showing that, in general terms, the innovation support policies were not able to reverse the clear regional concentration, with significant continuity of these initiatives focused on expanding opportunity for regions least developed in the country.